Novel coverage control algorithm for wireless sensor network - HAN Zhi-jie1; WU Zhi-bin2; WANG Ru-chuan3; SUN Li-juan3; XIAO Fu3 (Tongxin xuebao)
Firstly,in order to make an effective coverage control of WSN,the algorithm was proposed in WSN called AASR（adaptive adjustment of sensing radius）.Through the nodes choose the optimal coverage adaptively,node’s energy consumption could be reduced,and the coverage had been improved efficiency.Secondly,the result was presented in the simulation and analysis from respects of the effect of adjustment,energy consumption,as well as coverage redundancy.The result showes that AASR can effectively improve the survival time,reduce energy consumption,and increase cover-age.